2017
DOI: 10.1186/s12864-016-3385-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in mRNA expression and alternative pre-mRNA splicing associated with the effects of nutrition on apoptosis and spermatogenesis in the adult testis

Abstract: BackgroundThe effects of nutrition on testis mass in the sexually mature male have long been known, however, the cellular and molecular processes of the testis response to nutrition was not fully understood.MethodsWe tested whether the defects in spermatogenesis and increases in germ cell apoptosis in the testis that are induced by under-nutrition are associated with changes in mRNA expression and pre-mRNA alternative splicing using groups of 8 male sheep fed for a 10% increase or 10% decrease in body mass ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Mitogen-activated protein kinase kinase kinase 1 (MAP3K1), was mapped within a window that explained 1% of the variance in SM (BTA20: 22.18-23.18 Mb) and was of interest for its anti-and pro-apoptotic functions in germ cells 36 . Guan et al 37 found the MAP3K1 gene was differentially expressed in testis from underfed and well-fed sexually mature sheep, indicating it could be a marker of germ cell apoptosis and therefore change SC and the efficiency of sperm production. The vasoactive intestinal peptide (VIP; BTA9: 89.51-90.51 Mb window), another prioritized candidate gene mapped within a window for SC that explained 1.61% of the variance, is known to act directly on the testis, promoting the production of testosterone in mice and rats 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase kinase kinase 1 (MAP3K1), was mapped within a window that explained 1% of the variance in SM (BTA20: 22.18-23.18 Mb) and was of interest for its anti-and pro-apoptotic functions in germ cells 36 . Guan et al 37 found the MAP3K1 gene was differentially expressed in testis from underfed and well-fed sexually mature sheep, indicating it could be a marker of germ cell apoptosis and therefore change SC and the efficiency of sperm production. The vasoactive intestinal peptide (VIP; BTA9: 89.51-90.51 Mb window), another prioritized candidate gene mapped within a window for SC that explained 1.61% of the variance, is known to act directly on the testis, promoting the production of testosterone in mice and rats 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis in testicular germ cells is critical for spermatogenesis in mammals (1,2). It is believed that apoptosis plays an important role in the removal of overproduced, genetically abnormal, or accidentally damaged germ cells.…”
Section: Introductionmentioning
confidence: 99%
“…1). A total of 159 genes, including CREM and DDX4, were differentially spliced between dietary treatments, with functions related to RNA splicing and spermatogenesis (Guan et al 2017). Therefore, changes in alternative pre-mRNA splicing can help explain the effects on nutrition on spermatogenesis, but the effects of specific alternative types of splicing on spermatogenesis require further study.…”
Section: Nutrition Alternative Pre-mrna Splicing and Spermatogenesismentioning
confidence: 99%
“…In the testes affected by nutrition, we explored alternative splicing events using RNA-Seq and found that the alternatively spliced genes that differed between underfed and well-fed sheep were not related to apoptosis (Guan et al 2017), although one gene (HIPK3) was reported to be a member of a gene family that has been implicated in apoptosis. This result was surprising, because as indicated above, apoptosis is strongly associated with alternative splicing in other models in which nutrition was not the factor driving change in the testis.…”
Section: Nutrition Alternative Pre-mrna Splicing and Apoptosismentioning
confidence: 99%